POLITIK HUKUM DALAM KITAB UNDANG-UNDANG HUKUM PIDANA DENGAN HUKUM ISLAM TERHADAP TINDAK PIDANA PENISTAAN AGAMA - Irma Hayati Nasution; Syafruddin Kalo; Hasballah Thaib; Muhammad Ekaputra (Universitas Sumatera Utara, 2018)
ABSTRAK Since the era of reform of cases of irregularities in society more and more appear, one of which is the advent of the crime of defamation of religion in various forms, such as the emergence of irregularities in religious life in the community as opposed to the teachings and religious laws that already exist. These things can undermine the foundations of religious life existing community.Crime Settings Defamation of Religion in criminal law stipulated in the laws and regulations in Indonesia is contained in Article 156a of the Law of the Republic of Indonesia Number 1 Year 1946, hereinafter contained in Law No. 1 / PNPS / 1965 on Prevention of Abuse and or blasphemy bill in Articles 341-349 of the Criminal Code, and under Islamic law stipulated in the Qur'an surah an'am verse 108, Surah al-Maidah verse 57, Surah al-Luqman verse 6, Surah al-jaatsiyah verse 9. Keywords: Politics of Law, Criminal Code, Islamic Law, Blasphemy,